Analysis Analisis Daya Serap Air Paving Block Plastik Polypropylene - Ikram, Muhammad Fadhli Dzil; Utomo, Gunaedy; Indriani, Andi Marini (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Plastic waste in Balikpapan City accounts for 17% of the city's total waste production, ranking third after organic and paper waste. One category of waste that has received national and global attention is plastic waste. Plastic waste itself is difficult to decompose naturally and takes years, if the accumulation of plastic waste is allowed to drag on, it will cause many problems, such as disease and environmental pollution. Therefore, it is necessary to utilise plastic as one of the technological innovations in the field of construction, where this plastic can be used as a mixture in making paving. In this study, PP plastic was used as a substitute for cement in paving blocks. The purpose of this research is to assess whether paving blocks using a mixture of PP plastic and sand can fulfil the water absorption requirements according to SNI 03-0691-1996. The mixture used between PP plastic and sand is 10%, 30%, 50% with diamond shape with plastic melting temperature of 240○C. The absorption of paving blocks by utilising polypropylene plastic as a substitute for cement decreased as the percentage of PP plastic increased. The absorption of 10% plastic variation of the diamond meets quality B because it obtained an absorption value of 4.34%. While the addition of 30% and 50% plastic obtained a value below 3% which means it meets quality A in SNI 03-0691 (1996).